Implementation of solar cell booster to prevent damage to the electrical system and overcome CA N'T-Start Problems on PC2000-8 Units at PT PPA Jobsite Borneo Indobara - Margono, Margono; Suryana, Suryana; Sugiyanto, Sugiyanto; Putra, Arly Fiesnanda Baven (Universitas Wiralodra, 2024)
One of the critical problems that disrupted production achievement at the Putra Perkasa Abadi (PPA) Jobsite Borneo Indobara (BIB) mine was the breakdown of the unscheduled electrical system engine can't start on the PC2000-8 unit due to low battery voltage. The problem is behind the modification or improvement in the battery charging system of the PC2000-8 unit by adding components in the form of solar cells that function as backup supplies of electrical energy or battery boosters on the main battery of the unit. In this study, there is a novelty term, namely